Motion mode-driven adsorption by magnetically propelled MOF-based nanomotor. (June 2022) - Liu, X.; Dong, R.; Chen, Y.; Zhang, Q.; Yu, S.; Zhang, Z.; Hong, X.; Li, T.; Gao, M.; Cai, Y.
Abstract: Nanomotors have shown great potential in water purification, especially in pollutant adsorption, due to their active motion and nanoscale. We first studied the relationship between the motor's motion mode and its adsorption performance and proposed a novel, flexible and efficient strategy to regulate the nanomotor's adsorption performance, that is, motion mode switching. Inspired by a special Moroccan spider, which has two motion modes, we have prepared a new type of porous and rod-like nanomotor consisting of a Fe3 O4 -loaded cerium-based metal-organic frame (Fe3 O4 @Ce-MOF), which also has two motion modes: rotating or tumbling. By just switching the motion modes to bionic tumbling, the pollutant adsorption rate and the corresponding adsorption capacity of the nanomotor were greatly increased compared with the nanomotor in either a static state or engaged in rotational motion. In addition, these tumbling nanomotors can achieve both higher adsorption efficiency and lower energy consumption in comparison to motors with the rotational motion mode. Fluid dynamics simulation results further illustrate that this tumbling motion has strong fluid disturbances, which remarkably improves the contact efficiency of the pollutants in water, further enhancing the nanomotor's adsorption performance. Such a novel, flexible, and efficient strategy based on nanomotors brings a brand-new perspective for improving pollutant adsorption efficiency and holds great promise in future environmental remediation applications.